2021
DOI: 10.3390/metabo11020075
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pharmacokinetic Drug–Drug Interactions: A Review of the Mechanisms, In Vitro and In Silico Approaches

Abstract: Pharmacokinetic drug–drug interactions (DDIs) occur when a drug alters the absorption, transport, distribution, metabolism or excretion of a co-administered agent. The occurrence of pharmacokinetic DDIs may result in the increase or the decrease of drug concentrations, which can significantly affect the drug efficacy and safety in patients. Enzyme-mediated DDIs are of primary concern, while the transporter-mediated DDIs are less understood but also important. In this review, we presented an overview of the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 85 publications
0
27
0
6
Order By: Relevance
“…Novel and more structurally diverse FQs will continue to be developed for application to challenging bacterial infections with increasing antibiotic resistance. Predicting potential drug–drug interactions and quantifying the extent is a significant hurdle as new FQs enter the drug development phase [ 85 ]. While spacing the administration of the multivalent metals and FQs serves as a general guide in clinical practice, the effect of chelation on FQ pharmacokinetics remains highly variable (e.g., rufloxacin, which only shows a 15% decrease in AUC upon aluminum coadministration, Table 2 ) and patient compliance cannot be guaranteed.…”
Section: Resultsmentioning
confidence: 99%
“…Novel and more structurally diverse FQs will continue to be developed for application to challenging bacterial infections with increasing antibiotic resistance. Predicting potential drug–drug interactions and quantifying the extent is a significant hurdle as new FQs enter the drug development phase [ 85 ]. While spacing the administration of the multivalent metals and FQs serves as a general guide in clinical practice, the effect of chelation on FQ pharmacokinetics remains highly variable (e.g., rufloxacin, which only shows a 15% decrease in AUC upon aluminum coadministration, Table 2 ) and patient compliance cannot be guaranteed.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacokinetic interactions of practical importance are mainly based on changes in drug absorption and metabolism [42,45,46]. Our study showed that the co-administration of morphine and sorafenib resulted in a higher exposure of sorafenib when compared to sorafenib alone.…”
Section: The Influence Of Morphine On the Pharmacokinetics Of Sorafen...mentioning
confidence: 65%
“…18 Several assessments (in vitro, clinical, or modeling and simulation) are used to assess the risk of transporters based DDI and to minimize the possibility of consequential safety/ efficacy concerns in later development phases. [19][20][21][22] Each of these assessments has its own advantages and limitations in terms of applications, throughput, resource requirement, and sample analysis. Many of these assays are complimentary and can be utilized at different times during drug development.…”
Section: Articlementioning
confidence: 99%